2012
DOI: 10.5688/ajpe76582
|View full text |Cite
|
Sign up to set email alerts
|

An Online Knowledge Resource and Questionnaires as a Continuing Pharmacy Education Tool to Document Reflective Learning

Abstract: Objective. To assess the use of an electronic knowledge resource to document continuing education activities and reveal educational needs of practicing pharmacists. Methods. Over a 38-week period, 67 e-mails were sent to 6,500 Canadian Pharmacists Association (CPhA) members. Each e-mail contained a link to an e-Therapeutics1 Highlight, a factual excerpt of selected content from an online drug and therapeutic knowledge resource. Participants were then prompted to complete a pop-up questionnaire. Results. Member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…[14][15][16][17][18] Multiple challenges to team integration have also been identified in the literature. 3 However, few studies have examined the experiences or learning needs of pharmacists who are actively attempting to evolve their primary care practices in the real world.…”
mentioning
confidence: 99%
“…[14][15][16][17][18] Multiple challenges to team integration have also been identified in the literature. 3 However, few studies have examined the experiences or learning needs of pharmacists who are actively attempting to evolve their primary care practices in the real world.…”
mentioning
confidence: 99%
“…The district wise participation of the community pharmacists are shown in Figure 1 This study was performed to measure how effective was the CPE provided in knowledge enhancement, improvement in attitude and practice to the community pharmacist belonging to selected districts of Kerala and Tamilnadu. There are different ways of incorporating continuing education to the pharmacist, Budzinski et.al reported that reading highlight excerpts and completing Web-based questionnaires was found to be effective mode of continuing education 7 and another study published by Conte shown that even though pharmacists are interested to participate positively in web lectures, lack of technological and internet skills among community pharmacist would direct them more towards live sessions. 8 In India, every pharmacy yet to even hold an internet connection, we adopted this method of delivery of live lectures, issue of leaflets and revision after one week as the effective method of providing continuing education.…”
Section: Resultsmentioning
confidence: 99%
“…11,12 The fact that P1 students felt more confident in assigning BUDs (Q4) and using a spectrophotometer (Q9) is probably due to the fact they were doing those activities on a weekly basis compared to the P3 students who had a limited number of compounds during the semester.…”
Section: A J P Ementioning
confidence: 99%
“…Students may have rushed to perform the analysis and just report the results instead of reflecting on their results and how their work may have caused any errors. 8,11,12 The P3 laboratory time was in the afternoon, and many times students would stay later to finish their work at their own pace. The P3 students had also completed analyses in the other PCL courses prior to this year, and again had time to reflect on its significance.…”
Section: A J P Ementioning
confidence: 99%